Entamoeba histolytica thioredoxin reductase: Molecular and functional characterization of its atypical properties - Arias, Diego G.; Regner, Erika L.; Iglesias, Alberto A.; Guerrero, Sergio A. (Biochimica et biophysica acta, 2012)
Entamoeba histolytica, an intestinal protozoan that is the causative agent of amoebiasis, is exposed to elevated amounts of highly toxic reactive oxygen and nitrogen species during tissue invasion. Thioredoxin reductase catalyzes the reversible transfer of reducing equivalents between NADPH and thioredoxin, a small protein that plays key metabolic functions in maintaining the intracellular redox balance. The present work deals with in vitro steady state kinetic studies aimed to reach a better understanding of the kinetic and structural properties of thioredoxin reductase from E. histolytica (EhTRXR). Our results support that native EhTRXR is a homodimeric covalent protein that is able to catalyze the NAD(P)H-dependent reduction of amoebic thioredoxins and S‐nitrosothiols. In addition, the enzyme exhibited NAD(P)H dependent oxidase activity, which generates hydrogen peroxide from molecular oxygen. The enzyme can reduce compounds like methylene blue, quinones, ferricyanide or nitro-derivatives; all alternative substrates displaying a relative high capacity to inhibit disulfide reductase activity of EhTRXR. Interestingly, EhTRXR exhibited kinetic and structural properties that differ from other low molecular weight TRXR. The TRX system could play an important role in the parasite defense against reactive species. The latter should be critical during the extra intestinal phase of the amoebic infection. So far we know, this is the first in depth characterization of EhTRXR activity and functionality. ► The amoebic enzyme can use NADPH or NADH as substrates in μM concentrations. ► EhTRXR catalyzes the thioredoxin-independent reduction of S‐nitrosothiols. ► EhTRXR can use non-physiological substrates with similar catalytic efficiency.